Improving Software Quality Attributes of PS Using Stylecop (Global Journal of Computer Science and Technology, 2013)
Software product quality improvement is a desired attribute and a strenuous effort is required to achieve that Static Code Analysis SCA is used to find coding bugs Stylecop is an SCA tool from Microsoft In this paper SCA and stylecop usages are discussed Also a comparison of Software Testing software Metrics Source Code Analysis SCA is done Product PS designed by author1 and author2 is introduced PS application is analyzed using static SCA tool Stylecop After analysis recommendations were applied to PS The results showed improved software quality attributes
Keywords: SCA; PS; stylecop; software quality